PERANAN HUKUM ADAT DALAM MENJAGA DAN MELESTARIKAN HUTAN DI DESA METULANG KECAMATAN KAYAN SELATAN KABUPATEN MALINAU PROPINSI KALIMANTAN UTARA - Subiakto, Wildan Deki; Bakrie, Ismail (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
The Roles of Customary Law in Forest Management and Protection in Metulang Village, South Kayan District, Malinau Regency, North Borneo Province. The challenges of forest management and protection In Indonesia often come from local community who live around the forest. However, some studies have argued that customary practices of local community will support sustainable forest management.This research was to study 'how do local people and their customary law protect and manage their forest as well as to analyze determinant factors of customary law applied in forest management and protection Kenyah Dayak community in Metulang Village.This research takes place on Metulang Village, South Kayan District, Malinau Regency, North Borneo Province, backgrounded by the effort of conservation which is done by a group of society, meanwhile the deforestation is happening continuously.The methods used in this research a survey method with purposive sampling technique in collection data and implemented in the Metulang Village predominantly Kenyah Dayak (North Borneo). Data was collected through field observation, interviews and questionnaire with 35 respondents from indigenous Metulang Village.Based on the results of the questionnaire data processing to determine the role of customary law in protecting and preserving the forest in the Metulang Village each question item shows the average percentage above 70%, which means respondents in the Metulang Village agreed that customary law in the Village Metulang role in protecting and sustaining forest management.As for the activities of the community activities that support the conservation of forests in accordance with the customary rules applicable, indigenous Metulang Village classify land based approach on land use, location and types of natural resources that are important to society, local wisdom and traditional rules, namely : residential areas, land agricultural, forests and historic sites/culture. For the management of natural resources according to customary rules in the Metulang Village set includes : clearing agricultural land, forest, protected forest custom, wood extraction, retrieval cane, fruit orchards, taking agarwood, and forests burning.